An exploration of social challenges encountered by learners in Mohlakeng Schools in Rand-west municipality in Gauteng province of South Africa. - Mokoena, Prudence Onkarabile (My University, 2023)
There are countless social challenges in South African schools, such as poverty, violence, homeless, teen parenting, substance abuse, child abuse and youth suicide, which complicate learners’ efforts to learning. This study explored and described the social challenges that affect selected learners and their academic performance in Mohlakeng School in Rand-west municipality, Gauteng, South Africa. The study was positioned within an interpretivist paradigm using the qualitative research approach. The sample was fifteen (15) grade 11 and 12 learners from School in Mohlakeng and they were selected using non-probability purposive sampling. Data was collected using semi-structured telephonic interviews via an interview guide and analysed using the thematic data analysis method. Key findings in relation to the social challenges that learners experience that have an impact on their academic performance included academic challenges at school and unpleasant home circumstances. In terms of the coping strategies that learners adopted, the study found that learners did not have the necessary resources to cope, while others adopted various coping mechanisms. The key findings in terms of the support needs of learners were that 8 out of 15 learners needed extra academic support, 2 out of 15 learners thought about future prospects to deal with their social challenges, while for one participant it was important to mend family relationships and receive support from family. In terms of support, 9 out of 15 learners received support from families, while the other six participants did not receive support. These findings have implications for social work practice, the department of education, policy formation as well as future research.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts to the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2023
Keywords: Social Work; Mohlakeng School; Social challenges; South African schools; Academic challenges; Grade eleven and twelve learners